A Dose of Truth: A Qualitative Assessment of Reactions to Messages about Fentanyl for People Who Use Drugs. (21st March 2023) - Fernandez, Priscilla; Azucar, Danny; Zambole, Kim
Abstract: Background: Fentanyl-related overdoses are occurring at alarming rates and developing campaigns to increase awareness about fentanyl and harm-reduction strategies is critical. A Dose of Truth is an educational campaign aiming to increase knowledge about the threat of fentanyl and risk of exposure among people who use drugs (PWUD). The current study tests preliminary concepts and messages for the campaign. Methods: Twenty-one one-on-one interviews were conducted with young adults ages 18-35 who use drugs. Participants discussed knowledge of fentanyl and perceived risk of exposure, and provided feedback on four concepts. Thematic analysis of transcripts generated insights about promising approaches and topics. Results: Findings demonstrated that fentanyl awareness is growing among PWUD, but they perceive low risk of exposure because they trust a source. Messaging that challenged that trust, by highlighting that contaminated drug supplies are increasingly widespread, made personal risk salient. Additionally, messaging conveyed through a personal narrative that encouraged carrying naloxone to protect friends was perceived as personally relevant. Conclusions: While opioid- and fentanyl-related campaigns exist, few have used an evidence-based process to guide campaign development. Addressing gaps in knowledge and developing messages that are personally relevant are foundational steps in creating effective campaigns on fentanyl and other substances.